ANALISIS FAKTOR INTERNAL DAN EKSTERNAL DALAM PERCEPATAN PENURUNAN STUNTING: STUDI KUALITATIF DI KABUPATEN BOGOR Internal and External Factor Analysis of Stunting Reduction Acceleration: A Qualitative Study in Bogor District - Irmaida Irmaida; Dodik Briawan; Drajat Martianto (Media Gizi Indonesia, 2021)
Bogor District is one of the priority districts for stunting interventions. The stunting rate in Bogor District was 28.29%. The district government should implement stunting reduction policies that referring to the national movement of nutrition improvement acceleration and the stunting programs convergence. Regional autonomy gives authority to the regions to regulate and implement policies. This study aimed to analyze the internal and external factors of the Bogor District Government that aff ecting the implementation of stunting reduction programs It was a qualitative study in Bogor District. Primary data were collected using interview guidelines to nine offi cials of the Bogor District Government agency related to the stunting program in Bogor District. Secondary data were collected using desk review. Data were analyzed using Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) analysis. The results showed that total score of IFE is 2.96 and EFE scores is 2.94. Bogor District Government can optimally use its strengths and cut its weaknesses in the internal program. Likewise, Bogor District Government have taken advantage of external opportunities and avoided threats.